Anastomotic stenosis following proximal gastrectomy with single flap valvulopasty successfully managed with endoscopic stricturotomy: a case report - Tian, Yuan; Shao, Qiankun; Chen, Qiang; Peng, Wei; Ren, Rui; Gong, Wei; Liu, Tianhua; Zhu, Jianhong; Wu, Yongyou (Frontiers in Surgery, 2023)
Background Due to its nutritional advantages over total gastrectomy, proximal gastrectomy (PG) with anti-reflux techniques has gained significant attention in East Asian countries in recent years. The double flap technique (DFT) and modified side overlap and fundoplication by Yamashita (mSOFY) are two promising anti-reflux interventions following PG. However, anastomotic stenosis after DFT and gastroesophageal reflux after mSOFY have been reported in several patients. To address these concerns, a hybrid reconstruction procedure was designed, namely, right-sided overlap with single flap valvulopasty (ROSF), for proximal gastrectomy, with the aim of reducing anastomotic stricture and reflux. Among the 38 patients who underwent ROSF at our hospital, one developed Stooler grade II anastomotic stenosis. Herein, we present the successful management of this patient through endoscopic stricturotomy (ES). Case summary A 72-year-old female complaining of “epigastric pain and discomfort for more than 1 month” was diagnosed with adenocarcinoma of the esophagogastric junction (Siewert type II). She underwent laparoscopic-assisted PG and ROSF procedures at our hospital and recovered well after surgery. However, she started experiencing progressive difficulty in eating and vomiting approximately 3 weeks after the intervention. Endoscopy revealed Stooler grade II esophagogastric anastomotic stenosis. ES with insulated tip (IT) Knife nano was eventually performed, and the patient was able to resume a normal diet without experiencing any discomfort during the 5-month follow-up period. Conclusion Endoscopic stricturotomy using IT Knife nano successfully treated anastomotic stenosis following ROSF with no associated complications. Thus, ES to treat anastomotic stenosis after PG with valvulopasty can be considered a safe option and should be performed in centers with the required expertise.